1991
DOI: 10.1111/j.1540-8159.1991.tb02863.x
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography to Improve Positioning of Radiofrequency Ablation Catheters in Left‐Sided Wolff‐Parkinson‐White Syndrome

Abstract: Two patients with the Wolff-Parkinson-White syndrome who underwent successful radiofrequency catheter ablation of their left-sided bypass tracts are described. Transesophageal echocardiography, a relatively new echocardiographic technique, was utilized in both patients and provided excellent visualization of intracardiac anatomy as well as the catheter tip. Transesophageal echocardiography was also synergistic with fluoroscopy and the intracardiac electrogram in providing more precise catheter placement. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The New England Journal of Medicine lation, 148 and angioplasty for aortic coarctation 123 but is not necessary for these procedures.…”
Section: Ramentioning
confidence: 99%
“…The New England Journal of Medicine lation, 148 and angioplasty for aortic coarctation 123 but is not necessary for these procedures.…”
Section: Ramentioning
confidence: 99%
“…Several studies have demonstrated the utility of intracardiac ultrasound for guiding cardiac ablation therapy [11][12][13] and visualizing thermal lesions in vitro. 10,14 A recent study by Epstein and colleagues 15 compared intracardiac ultrasound to fluoroscopy guidance for creating linear right atrial lesions in a canine model and showed that intracardiac ultrasound significantly improved targeting, energy delivery, and lesion formation.…”
Section: Comparison With Other Imaging Modalitiesmentioning
confidence: 99%
“…Several investigators have reported the use of transesophageal echocardiography during interventional catheterization procedures [16][17][18][19][20][21][22]. In our experience, transesophageal echocardiography was an integral part of the procedure.…”
Section: Discussionmentioning
confidence: 92%